New species and new geographic record of Candolleomyces (Psathyrellaceae, Agaricales) from India - Nayana, P.k.; Pradeep, C.k. (Phytotaxa, 2025)
Two unique species of Candolleomyces were identified during our extensive investigation on the diversity of psathyrelloid mushrooms in Kerala State, India. Candolleomyces gregalis is new to science, and C. typhae is a new geographic record. The morphological investigations in conjunction with multigene phylogenetic analyses of a combined nucleotide sequence dataset for the internal transcribed spacer (nrITS) and the large subunit (nrLSU) of nuclear ribosomal DNA were employed to identify and characterize these taxa. Herein, we fully describe and illustrate C. gregalis and provide updated descriptions and distributional data for C. typhae.